Environment-friendly clay coagulant aid for wastewater treatment - Sharmin Sultana (SpringerOpen, 2021)
Abstract Wastewater management and its environment-friendly applications seem to be very complicated associated with chemical effects due to their dynamic characteristics for developing countries. Most of the world's agencies or countries have been treated wastewater using chemical coagulants which have contributed to other environmental complications. Considering the impacts of chemical coagulation, this study is novel research to identify alternative components that would be applied as a natural coagulant. The present study was conducted using two different regional clays as coagulants which were collected from Portugal and Bangladesh's Patuakhali coastal area. The clay coagulant applications were applied to investigate the removal efficiency of physical properties (turbidity), chemical properties (pH and COD), and heavy metals (Cr, Cd, Ni, and Pb) from wastewater. Comparatively, the highest removal efficiency was examined by the coastal clay of Patuakhali. This soil is also easily available in the local context and can be economically viable.